Magnitude of workplace violence and associated factors among healthcare professionals in East Africa: A systematic review and meta-analysis - Yeshiambaw Eshetie; Astewle Andargie Baye; Mengistu Ewunetu; Gashaw Kerebeh; Worku Necho Asferie; Demewoz Kefale (PLoS ONE, 2025)
Introduction Workplace violence refers to violent acts that occur in the workplace against employees while they are delivering services to consumers. This phenomenon is an invasive and alarming issue affecting employees worldwide, posing both implicit and explicit threats to their health, safety and well-being. According to a World Health Organization report and study findings, 20% to 38% of healthcare workers have experienced physical violence at some point during their careers, compared to employees in other sectors. This study aimed to assess the pooled magnitude of workplace violence and to identify its associated factors among healthcare professionals in East Africa. Method The study protocol was registered with PROSPERO under registration number CRD42024552266. An extensive electronic database search was conducted from August 10–31, 2024, using PubMed, Google Scholar, Web of Science, and manual Google searches. The extracted data were exported into STATA version 17 for analysis. A weighted inverse-variance random-effects model was used to calculate the pooled magnitude of workplace violence and to determine the impact of predictors on the workplace violence. Publication bias was checked by a funnel plot and Egger’s test. Heterogeneity was assessed using I2 statistic and Galbraith plot. Subgroup and sensitivity analyses were conducted to investigate the sources of heterogeneity. Results A total of 25 studies involving 9,648 participants were included in this study. The pooled magnitude of workplace violence was 55.64% (95% CI: 48.32, 62.96; I2 = 97%, p < 0.01). Factors significantly associated with workplace violence included working in the emergency department (AOR = 4.3, 95% CI: 3.22, 5.39), younger age (AOR = 3.01, 95% CI: 1.42, 4.60), less work experience (AOR = 5.14, 95% CI: 2.67, 7.61), being female (AOR = 2.74, 95% CI: 1.54, 3.95), and alcohol consumption (AOR = 3.17, 95% CI: 1.52, 4.83). Conclusion The magnitude of workplace violence in the region was relatively prevalent, with significantly higher odds among emergency department staff, younger healthcare professionals, those with less work experience, female professionals, and individual reporting alcohol consumption.